Effect of Cortical Bone Thickness on Detection of Intraosseous Lesions by Ultrasonography - Sadaf Adibi; Alireza Shakibafard; Zohreh Karimi Sarvestani; Najmeh Saadat; Leila Khojastepour (Radiology Research and Practice)
Background. Usefulness of ultrasound (US) in detection of intrabony lesions has been showed. A cortical bone perforation or a very thin and intact cortical bone is prerequisite for this purpose. Objective. The current in vitro study was aimed at measuring the cut-off thickness of the overlying cortical bone which allows ultrasonic assessment of bony defects. Materials and Methods. 20 bovine scapula blocks were obtained. Samples were numbered from 1 to 20. In each sample, 5 artificial lesions were made. The lesions were made in order to increase the overlying bone thickness, from 0.1 mm in the first sample to 2 mm in the last one (with 0.1 mm interval). After that, the samples underwent ultrasound examinations by two practicing radiologists. Results. All five lesions in samples numbered 1 to 11 were detected as hypoechoic area. Cortical bone thickness more than 1.1 mm resulted in a failure in the detection of central lesions. Conclusion. We can conclude that neither bony perforation nor very thin cortical bones are needed to consider US to be an effective imaging technique in the evaluation of bony lesion.